A method for preparing a self-flowing high-efficiency fast-dissolving drag-reducing fracturing fluid system

By combining water-soluble polymers, fluorine-containing monomers, and nanomaterials, a self-flowing, high-efficiency, fast-dissolving, and drag-reducing fracturing fluid was prepared. This solved the stability problem of fracturing fluid under high temperature, high salt, and strong shear conditions, improved fracturing effect and flowback efficiency, and reduced environmental impact.

CN118813234BActive Publication Date: 2025-01-07YANAN JUNDE PETROLEUM ENG TECH SERVICE CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411297978.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2025-01-07
Estimated Expiration
2044-09-18

AI Technical Summary

Technical Problem

Existing fracturing fluids are prone to degradation at high temperatures, have compromised stability in high-salt environments, and suffer from molecular chain breakage under strong shearing, leading to a loss of drag reduction effect.

Method used

A self-flowing, high-efficiency, fast-dissolving, and drag-reducing fracturing fluid system was prepared by combining water-soluble polymers, fluorinated monomer modifiers, and nanomaterials through free radical polymerization and chemical bonding to form a polymer film. The pH value was adjusted to 7-8 to optimize the performance of the fracturing fluid.

Benefits of technology

Maintaining the stability and fluidity of fracturing fluid under high temperature, high salinity and strong shear conditions improves fracturing efficiency, reduces the risk of sedimentation and blockage, promotes flowback, and reduces environmental impact.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118813234B_ABST
    Figure CN118813234B_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a self-flowing high-efficiency fast-dissolving drag-reducing fracturing fluid system. The following components in weight percentage are added into a reactor in sequence: 45% to 50% of the water-soluble high molecular polymer solution obtained in step one, 27% to 29% of the fluorine-containing monomer modifier solution obtained in step two, 11% to 12% of the polymer nanocomposite material obtained in step four, 2% to 3% of a dispersant, 1.8% to 1.9% of an inorganic salt, 1.2% to 1.3% of a cross-linking agent, and the balance is water. The invention discloses a method for preparing a self-flowing high-efficiency fast-dissolving drag-reducing fracturing fluid system. By adding a modifier into a nano material, a polymer film can be directly formed on the surface of the nano material by chemical bonding, thereby changing the surface properties thereof, so that the stability and shear resistance of the fracturing fluid are maintained at high temperatures.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of oil and gas exploitation, and in particular to a method for preparing a self-flowing high-efficiency fast-dissolving drag-reducing fracturing fluid system. Background Art

[0002] As a recognized clean fossil energy, the exploitation of shale gas is of great significance for alleviating energy pressure and reducing carbon emissions. Currently, shale gas resources are abundant and have great exploitation value. However, unlike conventional natural gas, shale gas is stored in shale formations with very small pores and low permeability, making it difficult to exploit. Hydraulic fracturing technology must be used to improve the efficiency of exploitation. Hydraulic fracturing technology injects fracturing fluid into the formation, expands the formation cracks and carries proppant into the cracks to prevent the cracks from closing, thereby improving the ability of shale gas to seep into the wellbore.

[0003] The current fracturing fluid preparation technology requires the addition of efficient drag reducers during preparation. Through the efficient drag reducers and their surfactants or polymer components, they interact with the water and other material surfaces in the fracturing fluid, weakening the cohesion between liquid molecules, thereby significantly reducing the viscosity of the fracturing fluid. After the viscosity is reduced, the self-flow rate is increased, thereby improving the pumping efficiency and the overall effect of the fracturing operation. Compared with natural polymer drag reducers such as guar gum and xanthan gum, traditional synthetic polymer drag reducers, such as certain polyacrylamide compounds, do have improved drag reduction performance. They can significantly reduce the viscosity of fracturing fluids and improve flow properties under certain conditions. However, under high temperature environments, these polymers are prone to degradation, resulting in a sharp decline in drag reduction effect; in high-salt environments, the increase in ionic strength will destroy the stability of the drag reducer molecules and affect their drag reduction performance; and under strong shear, the drag reducer molecular chains may break, which also leads to the loss of drag reduction effect. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing a self-flowing high-efficiency fast-dissolving drag-reducing fracturing fluid system, so as to solve the problems mentioned in the above background technology that these polymers are prone to degradation under high temperature environment, resulting in a sharp decline in drag reduction effect; in a high-salt environment, the increase in ionic strength will destroy the stability of the drag reducer molecules and affect its drag reduction performance; and under strong shearing action, the drag reducer molecular chains may break, which also leads to the loss of drag reduction effect.

[0005] To achieve the above object, the present invention provides the following technical solution: a method for preparing a self-flowing high-efficiency fast-dissolving drag-reducing fracturing fluid system, comprising the following production steps:

[0006] Step 1: adding a water-soluble polymer into water and stirring until the polymer is completely dissolved to obtain a water-soluble polymer solution;

[0007] Step 2: mixing the fluorinated monomer with an organic solvent and a surfactant to prepare a fluorinated monomer modifier solution through a free radical polymerization reaction;

[0008] Step 3: Adding a modifier to the nanomaterial can directly combine with the surface of the nanomaterial by chemical bonding and form a polymer film on the surface of the nanomaterial, thereby changing its surface properties and improving its compatibility with the polymer matrix;

[0009] Step 4: dissolving the modified nanomaterial and the polymer matrix in an organic solvent, mixing them evenly by ultrasonic means, and the sound wave range is 30kHz to 80kHz, and then volatilizing and drying the final solvent, and the drying temperature range is 30°C to 40°C, and finally obtaining a polymer nanocomposite material;

[0010] Step 5: Add the following components in weight percentage into the reactor in sequence: 45% to 50% of the water-soluble polymer solution obtained in step 1, 27% to 29% of the fluorine-containing monomer modifier solution obtained in step 2, 11% to 12% of the polymer nanocomposite material obtained in step 4, 2% to 3% of the dispersant, 1.8% to 1.9% of the inorganic salt, 1.2% to 1.3% of the cross-linking agent and the balance of water, stir and mix thoroughly to obtain a fracturing fluid;

[0011] Step 6: Use a pH regulator to adjust the pH value of the fracturing fluid to between 7 and 8;

[0012] Step 7: Filter the prepared fracturing fluid through a filter to remove impurities and undissolved particles, and then package it into a finished product.

[0013] As a preferred technical solution of the present invention, the water-soluble high molecular polymer adopts polyacrylamide monomer, and the mass ratio of polyacrylamide monomer to water is 3:1000.

[0014] As a preferred technical solution of the present invention, the organic solvent in step 2 is acetone, the fluorine-containing monomer is perfluoroacrylate, the surfactant is a fluorine-containing surfactant, and the mass ratio of the acetone, perfluoroacrylate and fluorine-containing surfactant is 30:12:7.

[0015] As a preferred technical solution of the present invention, the nano material is silicon dioxide nano material, the modifier is polyethylene glycol, and the mass ratio of the nano material to the modifier is 8:1.

[0016] As a preferred technical solution of the present invention, the polymer matrix adopts a mixture of epoxy resin and polyimide, and the mass ratio of the epoxy resin to the polyimide is 1:1.

[0017] As a preferred technical solution of the present invention, the organic solvent in step 4 is N,N-dimethylformamide, and the mass ratio of the pre-synthesized nanomaterial and the polymer matrix is ​​2:7.

[0018] As a preferred technical solution of the present invention, the pH regulator is sodium hydroxide and acetic acid solution.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] 1. The present invention adds fluorine-containing monomers. Due to their unique chemical properties, fluorine-containing monomers can significantly reduce the interfacial tension between the fracturing fluid and the formation rock. This reducing effect helps the fracturing fluid to penetrate into the formation better and improve the fracturing effect. The fluorine-containing monomer modifier solution is prepared by free radical polymerization reaction, which can help dissolve solid particles or insoluble substances in the fracturing fluid, reduce the risk of precipitation and blockage, and make the fracturing fluid have lower viscosity and good fluidity, improve the fracturing effect and promote backflow. The introduction of the fluorine-containing monomer modifier solution can enhance the hydrophobicity of the molecules, help reduce the interaction between water molecules and drag reducer molecules, thereby reducing the influence of salt ions on drag reducer molecules. At the same time, the fluorine-containing monomer modifier fluorine-containing monomer due to its unique chemical properties can introduce stable fluorocarbon bonds in the molecular chain. The bond energy of this bond is relatively high, making the fluorine-containing polymer not easy to break when subjected to shear force, thereby maintaining the integrity of the molecular structure, so that it can still maintain stable performance under high shear conditions.

[0021] 2. The present invention can directly form a layer of polymer film on the surface of the nanomaterial by chemical bonding by adding a modifier to the nanomaterial, thereby changing its surface properties and improving its compatibility with the polymer matrix. The polymer film serves as a bridge between the nanomaterial and the polymer matrix, and can significantly reduce the interfacial energy between the two, thereby enhancing the compatibility of the nanomaterial and the polymer matrix, and helps to maintain the stability and shear resistance of the fracturing fluid at high temperatures, while helping to reduce the agglomeration of the nanomaterial in the polymer matrix and improve the dispersion uniformity of the nanomaterial in the matrix.

[0022] 3. The present invention adjusts the pH value of the fracturing fluid to the range of 7-8 through a pH regulator. The pH value in this range helps to maintain the viscosity and rheological properties of the fracturing fluid, so that it can function stably during the construction process. Moreover, under the condition of a pH value of 7-8, the sand carrying capacity of the fracturing fluid will be optimized, which helps to more effectively transport the proppant to the target formation and improve the fracturing effect. At the same time, adjusting the pH value of the fracturing fluid to between 7-8 helps to reduce the potential impact on the environment during the fracturing process, such as reducing groundwater pollution. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a flow chart for preparing a self-flowing high-efficiency fast-dissolving drag-reducing fracturing fluid according to the present invention;

[0024] Figure 2 This is a data diagram of drag reduction test of various drag reducers of the present invention;

[0025] Figure 3 This is a diagram of a drag reduction test of various drag reducers of the present invention;

[0026] Among them: the experimental reagents added to the liquid in the measuring cup from left to right are JHFR-2 nano-composite liquid drag reducer, powder drag reducer, and oil-based drag reducer. DETAILED DESCRIPTION

[0027] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] See also Figure 1-3 The present invention provides a technical solution for the preparation of a self-flowing high-efficiency fast-dissolving drag-reducing fracturing fluid system:

[0029] In some specific embodiments of the present invention, the water-soluble high molecular polymer can enhance the suspension stability of the fracturing fluid, so that the proppant is better dispersed in the liquid, and at the same time can reduce the flow resistance of the fluid in the pipeline, improve the injection efficiency of the fracturing fluid, and after the fracturing operation is completed, it can also quickly degrade into small molecular substances to reduce damage to the formation. Compared with other materials of the same type, the water-soluble high molecular polymer usually has better temperature resistance, salt resistance, and shear resistance, and can maintain stable performance in a complex underground environment; further, the water-soluble high molecular polymer adopts polyacrylamide monomer, which is an important water-soluble high molecular polymer that can be quickly and evenly dissolved in water to form a stable polymer solution. This feature makes it easy to add it and evenly disperse it in the liquid when preparing the fracturing fluid. At the same time, polyacrylamide can significantly improve the sand carrying capacity, resistance reduction performance and gel breaking performance of the fracturing fluid. Specifically, the addition of polyacrylamide relative to other polymers can enable the fracturing fluid to better carry the proppant into the formation cracks, reduce the flow resistance of the fluid in the pipeline, and quickly degrade into small molecular substances after fracturing, reducing damage to the formation.

[0030] In some specific embodiments of the present invention, the fluorine-containing monomer has an extremely low surface tension, which can significantly reduce the surface tension of the fracturing fluid and improve its wettability and spreadability on the surface of the formation rock. This property helps the fracturing fluid to better penetrate into the formation cracks and improve the fracturing effect. The perfluoroacrylate has an extremely low surface energy and a high chemical stability, wherein the surface energy is the energy possessed by molecules in the surface layer of a substance, which reflects the strength of the interaction between molecules on the surface of the substance. Since the perfluoroacrylate molecule contains a large number of fluorine atoms, and the fluorine atoms have extremely strong electronegativity, the covalent bond between the fluorine atoms and the carbon atoms is very stable, and the interaction force between the fluorine atoms is also weak. This special molecular structure causes the surface energy of the perfluoroacrylate to be extremely low, that is, the interaction force between its surface molecules is very weak, making it difficult for other substances to adhere to or wet its surface, which enables it to exhibit excellent resistance in the fracturing fluid. Its unique fluorocarbon chain structure gives the modifier solution excellent hydrophobic and oleophobic properties, which helps to reduce the adsorption and loss of fracturing fluid in the formation and improve the fracturing efficiency; acetone, as an organic solvent, has good solubility for fluorinated monomers such as perfluoroacrylate, which can ensure that the components are fully mixed and evenly dispersed during the free radical polymerization reaction. Compared with other organic solvents, acetone has lower toxicity and is easy to recycle and handle. Using acetone as a solvent in the preparation of fracturing fluid helps to reduce pollution to the environment; fluorinated surfactants have extremely low surface tension and excellent wettability due to the strong electronegativity and small van der Waals radius of fluorine atoms. Compared with other surfactants, fluorinated surfactants can significantly reduce the surface tension of the liquid, improve the wettability and spreadability of the fracturing fluid on the surface of the formation rock, and help the fracturing fluid to better penetrate into the formation cracks.

[0031] In some specific embodiments of the present invention, nano-silica particles have a large specific surface area and surface energy, can be evenly dispersed in a polymer matrix, are not easy to agglomerate, and form a stable nano-composite structure. This structure can enhance the heat resistance and shear resistance of the polymer, and the chemical properties of silica are stable and are not easy to react with most chemical substances, thereby ensuring the long-term effectiveness of the fracturing fluid under complex geological conditions; polyethylene glycol is a highly hydrophilic polymer, and polyethylene glycol can be modified to the surface of nano-silica by chemical bonding to form a hydrophilic film on the surface of nano-silica, which can improve the dispersibility and stability of nanoparticles in water-based fracturing fluids, and can significantly improve the compatibility of nanomaterials with polymer matrices, reduce interfacial tension, and enhance the overall performance of fracturing fluids. Compared with some other modifiers, polyethylene glycol has lower toxicity and will not cause significant effects on the environment and organisms.

[0032] In some specific embodiments of the present invention, the polymer matrix adopts a mixture of epoxy resin and polyimide. Epoxy resin has excellent adhesion, chemical corrosion resistance and mechanical strength, while polyimide is known for its high thermal stability, excellent mechanical properties and wear resistance. The mixture of epoxy resin and polyimide can complement each other's advantages, so that the polymer nanocomposite material is not only further enhanced in strength, toughness, heat resistance, etc., but also can enhance the dispersibility and stability of nanomaterials in the matrix, thereby improving the overall performance of the composite material. Compared with other polymer matrices, the mixture of epoxy resin and polyimide has a higher thermal decomposition temperature and better thermal oxidation stability, can maintain good performance in a high temperature environment, and meet the high temperature requirements in the development of unconventional oil and gas resources such as shale gas. At the same time, it can make the composite material exhibit higher strength and toughness when subjected to pressure, shear force and impact load, which is beneficial to maintain the stability and sand carrying capacity of the fracturing fluid during the fracturing construction process.

[0033] In some specific embodiments of the present invention, during the fracturing construction process, the fracturing fluid needs to withstand the dual shear force from the formation and the pipeline. The fluorinated monomer modifier can enhance the intermolecular force of the fracturing fluid, so that it has better shear resistance, thereby maintaining the stability and effectiveness of the fracturing fluid during the construction process. Acetone is a polar solvent and has good solubility for the fluorinated monomer, which helps to evenly disperse and dissolve the reactants in the polymerization reaction, improve the reaction efficiency and the uniformity of the product. The fluorinated surfactant has excellent thermal stability and chemical stability due to its special molecular structure (fluorine atoms replace hydrogen atoms on the hydrophobic groups in ordinary surfactants to form CF bonds. Since the bond energy of the CF bond is greater than that of the CH bond, and the volume of the fluorine atom is large, it has a shielding effect on the CC bond), and has extremely high surface activity, which enables the fluorinated monomer to significantly reduce the surface tension of the solution at extremely low concentrations and promote the polymerization reaction.

[0034] In some specific embodiments of the present invention, since N,N-dimethylformamide has a moderate viscosity and good conductivity to sound waves, when ultrasonic mixing is used, the nanomaterial can be more effectively dispersed in the polymer matrix, which helps to reduce the agglomeration of the nanomaterial and improve the performance of the composite material. At the same time, N,N-dimethylformamide is relatively stable at room temperature and is not easy to decompose or produce harmful by-products, thereby ensuring the quality of the composite material.

[0035] In some specific embodiments of the present invention, the fracturing fluid having a pH value in the range of 7-8 helps to maintain the viscosity and rheological properties of the fracturing fluid, so that it can function stably during the construction process. Compared with overly acidic or overly alkaline fracturing fluids, fracturing fluids having a pH value in the range of 7-8 are less corrosive to equipment and pipelines, which helps to protect construction equipment and reduce maintenance costs.

[0036] In some specific embodiments of the present invention, the dispersant is a nonionic surfactant, which is in a nonionic state in an aqueous solution and has high stability. After being compounded with a fluorinated surfactant, the stability and weather resistance of the overall system can be further improved. The calcium chloride used in the inorganic salt has a relatively high density. When added to the fracturing fluid, the density of the fracturing fluid can be significantly increased, so that the fracturing fluid can further stabilize the supporting cracks or carry more proppant formations. Calcium chloride has excellent temperature resistance and can maintain the stability of its physical and chemical properties at higher temperatures. In contrast, some inorganic salts of the same type have poor thermal stability at high temperatures. The cross-linking agent is borate, which can quickly react with the high molecular polymer in the fracturing fluid in an aqueous solution to form a highly viscoelastic gel. This rapid cross-linking rate helps to quickly increase the viscosity and sand carrying capacity of the fracturing fluid during the fracturing process, thereby effectively supporting the cracks and preventing sand from flowing back. Compared with other types of cross-linking agents, borate cross-linking agents usually have a lower cost, which helps to reduce the overall operating cost. In addition, borate cross-linking agents cause relatively little damage to formations and reservoirs, which is of great significance for protecting reservoirs and improving recovery rates.

[0037] Embodiment 1, a method for preparing a self-flowing high-efficiency fast-dissolving drag-reducing fracturing fluid system, comprising the following steps:

[0038] Step 1: adding a water-soluble polymer into water and stirring until the polymer is completely dissolved to obtain a water-soluble polymer solution;

[0039] Step 2: mixing the fluorinated monomer with an organic solvent and a surfactant to prepare a fluorinated monomer modifier solution through a free radical polymerization reaction;

[0040] Step 3: Adding a modifier to the nanomaterial can directly combine with the surface of the nanomaterial by chemical bonding and form a polymer film on the surface of the nanomaterial, thereby changing its surface properties and improving its compatibility with the polymer matrix;

[0041] Step 4: dissolving the modified nanomaterial and the polymer matrix in an organic solvent, mixing them evenly by ultrasonic means, and the sound wave range is 30kHz to 80kHz, and then volatilizing and drying the final solvent, and the drying temperature range is 30°C to 40°C, and finally obtaining a polymer nanocomposite material;

[0042] Step 5: Add the following components in weight percentage into the reactor in sequence: 45% of the water-soluble polymer solution obtained in step 1, 27% of the fluorinated monomer modifier solution obtained in step 2, 11% of the polymer nanocomposite material obtained in step 4, 2% of the dispersant, 1.8% of the inorganic salt, 1.2% of the cross-linking agent and the balance of water, stir and mix thoroughly to obtain a fracturing fluid;

[0043] Step 6: Use a pH regulator to adjust the pH value of the fracturing fluid to between 7 and 8;

[0044] Step 7: Filter the prepared fracturing fluid through a filter to remove impurities and undissolved particles, and then package it into a finished product.

[0045] Example 2, based on Example 1, a method for preparing a self-flowing high-efficiency fast-dissolving drag-reducing fracturing fluid system comprises the following steps:

[0046] Step 1: adding a water-soluble polymer into water and stirring until the polymer is completely dissolved to obtain a water-soluble polymer solution;

[0047] Step 2: mixing the fluorinated monomer with an organic solvent and a surfactant to prepare a fluorinated monomer modifier solution through a free radical polymerization reaction;

[0048] Step 3: Adding a modifier to the nanomaterial can directly combine with the surface of the nanomaterial by chemical bonding and form a polymer film on the surface of the nanomaterial, thereby changing its surface properties and improving its compatibility with the polymer matrix;

[0049] Step 4: dissolving the modified nanomaterial and the polymer matrix in an organic solvent, mixing them evenly by ultrasonic means, and the sound wave range is 30kHz to 80kHz, and then volatilizing and drying the final solvent, and the drying temperature range is 30°C to 40°C, and finally obtaining a polymer nanocomposite material;

[0050] Step 5: Add the following components in weight percentage into the reactor in sequence: 50% of the water-soluble polymer solution obtained in step 1, 27% of the fluorinated monomer modifier solution obtained in step 2, 11% of the polymer nanocomposite material obtained in step 4, 2% of the dispersant, 1.8% of the inorganic salt, 1.2% of the cross-linking agent and the balance of water, stir and mix thoroughly to obtain a fracturing fluid;

[0051] Step 6: Use a pH regulator to adjust the pH value of the fracturing fluid to between 7 and 8;

[0052] Step 7: Filter the prepared fracturing fluid through a filter to remove impurities and undissolved particles, and then package it into a finished product.

[0053] Example 3, based on Example 1, a method for preparing a self-flowing high-efficiency fast-dissolving drag-reducing fracturing fluid system comprises the following steps:

[0054] Step 1: adding a water-soluble polymer into water and stirring until the polymer is completely dissolved to obtain a water-soluble polymer solution;

[0055] Step 2: mixing the fluorinated monomer with an organic solvent and a surfactant to prepare a fluorinated monomer modifier solution through a free radical polymerization reaction;

[0056] Step 3: Adding a modifier to the nanomaterial can directly combine with the surface of the nanomaterial by chemical bonding and form a polymer film on the surface of the nanomaterial, thereby changing its surface properties and improving its compatibility with the polymer matrix;

[0057] Step 4: dissolving the modified nanomaterial and the polymer matrix in an organic solvent, mixing them evenly by ultrasonic means, and the sound wave range is 30kHz to 80kHz, and then volatilizing and drying the final solvent, and the drying temperature range is 30°C to 40°C, and finally obtaining a polymer nanocomposite material;

[0058] Step 5: Add the following components in weight percentage into the reactor in sequence: 45% of the water-soluble polymer solution obtained in step 1, 29% of the fluorinated monomer modifier solution obtained in step 2, 11% of the polymer nanocomposite material obtained in step 4, 2% of the dispersant, 1.8% of the inorganic salt, 1.2% of the cross-linking agent and the balance of water, stir and mix thoroughly to obtain a fracturing fluid;

[0059] Step 6: Use a pH regulator to adjust the pH value of the fracturing fluid to between 7 and 8;

[0060] Step 7: Filter the prepared fracturing fluid through a filter to remove impurities and undissolved particles, and then package it into a finished product.

[0061] Example 4, based on Example 3, a method for preparing a self-flowing high-efficiency fast-dissolving drag-reducing fracturing fluid system comprises the following steps:

[0062] Step 1: adding a water-soluble polymer into water and stirring until the polymer is completely dissolved to obtain a water-soluble polymer solution;

[0063] Step 2: mixing the fluorinated monomer with an organic solvent and a surfactant to prepare a fluorinated monomer modifier solution through a free radical polymerization reaction;

[0064] Step 3: Adding a modifier to the nanomaterial can directly combine with the surface of the nanomaterial by chemical bonding and form a polymer film on the surface of the nanomaterial, thereby changing its surface properties and improving its compatibility with the polymer matrix;

[0065] Step 4: dissolving the modified nanomaterial and the polymer matrix in an organic solvent, mixing them evenly by ultrasonic means, and the sound wave range is 30kHz to 80kHz, and then volatilizing and drying the final solvent, and the drying temperature range is 30°C to 40°C, and finally obtaining a polymer nanocomposite material;

[0066] Step 5: Add the following components in weight percentage into the reactor in sequence: 45% of the water-soluble polymer solution obtained in step 1, 29% of the fluorinated monomer modifier solution obtained in step 2, 12% of the polymer nanocomposite material obtained in step 4, 2% of the dispersant, 1.9% of the inorganic salt, 1.2% of the cross-linking agent and the balance of water, stir and mix thoroughly to obtain a fracturing fluid;

[0067] Step 6: Use a pH regulator to adjust the pH value of the fracturing fluid to between 7 and 8;

[0068] Step 7: Filter the prepared fracturing fluid through a filter to remove impurities and undissolved particles, and then package it into a finished product.

[0069] Example 5, based on Example 4, a method for preparing a self-flowing high-efficiency fast-dissolving drag-reducing fracturing fluid system comprises the following steps:

[0070] Step 1: adding a water-soluble polymer into water and stirring until the polymer is completely dissolved to obtain a water-soluble polymer solution;

[0071] Step 2: mixing the fluorinated monomer with an organic solvent and a surfactant to prepare a fluorinated monomer modifier solution through a free radical polymerization reaction;

[0072] Step 3: Adding a modifier to the nanomaterial can directly combine with the surface of the nanomaterial by chemical bonding and form a polymer film on the surface of the nanomaterial, thereby changing its surface properties and improving its compatibility with the polymer matrix;

[0073] Step 4: dissolving the modified nanomaterial and the polymer matrix in an organic solvent, mixing them evenly by ultrasonic means, and the sound wave range is 30kHz to 80kHz, and then volatilizing and drying the final solvent, and the drying temperature range is 30°C to 40°C, and finally obtaining a polymer nanocomposite material;

[0074] Step 5: Add the following components in weight percentage into the reactor in sequence: 45% of the water-soluble polymer solution obtained in step 1, 29% of the fluorinated monomer modifier solution obtained in step 2, 12% of the polymer nanocomposite material obtained in step 4, 3% of the dispersant, 1.8% of the inorganic salt, 1.2% of the cross-linking agent and the balance of water, stir and mix thoroughly to obtain a fracturing fluid;

[0075] Step 6: Use a pH regulator to adjust the pH value of the fracturing fluid to between 7 and 8;

[0076] Step 7: Filter the prepared fracturing fluid through a filter to remove impurities and undissolved particles, and then package it into a finished product.

[0077] Example 6, based on Example 5, a method for preparing a self-flowing high-efficiency fast-dissolving drag-reducing fracturing fluid system comprises the following steps:

[0078] Step 1: adding a water-soluble polymer into water and stirring until the polymer is completely dissolved to obtain a water-soluble polymer solution;

[0079] Step 2: mixing the fluorinated monomer with an organic solvent and a surfactant to prepare a fluorinated monomer modifier solution through a free radical polymerization reaction;

[0080] Step 3: Adding a modifier to the nanomaterial can directly combine with the surface of the nanomaterial by chemical bonding and form a polymer film on the surface of the nanomaterial, thereby changing its surface properties and improving its compatibility with the polymer matrix;

[0081] Step 4: dissolving the modified nanomaterial and the polymer matrix in an organic solvent, mixing them evenly by ultrasonic means, and the sound wave range is 30kHz to 80kHz, and then volatilizing and drying the final solvent, and the drying temperature range is 30°C to 40°C, and finally obtaining a polymer nanocomposite material;

[0082] Step 5: Add the following components in weight percentage into the reactor in sequence: 45% of the water-soluble polymer solution obtained in step 1, 29% of the fluorinated monomer modifier solution obtained in step 2, 12% of the polymer nanocomposite material obtained in step 4, 3% of the dispersant, 1.9% of the inorganic salt, 1.3% of the cross-linking agent and the balance of water, stir and mix thoroughly to obtain a fracturing fluid;

[0083] Step 6: Use a pH regulator to adjust the pH value of the fracturing fluid to between 7 and 8;

[0084] Step 7: Filter the prepared fracturing fluid through a filter to remove impurities and undissolved particles, and then package it into a finished product.

[0085] Comparative Example 1: Based on Example 6, no water-soluble high molecular polymer solution was added, and the rest was the same as Example 6.

[0086] Comparative Example 2: Based on Example 6, no fluorine-containing monomer modifier is added, only a surfactant is added, and the surfactant is an ethoxylated Gemini quaternary ammonium salt cationic surfactant, and the rest is the same as Example 6.

[0087] Comparative Example 3: Based on Example 6, no polymer nanocomposite material was added, and the rest was the same as Example 6.

[0088] The present invention discloses a method for preparing a self-flowing high-efficiency fast-dissolving drag-reducing fracturing fluid system. The fracturing fluids obtained in Examples 1-6 and Comparative Examples 1-3 are subjected to performance tests. According to the corresponding testing standards, the performance test results of the fracturing fluids are as follows:

[0089]

[0090] According to the above data, it can be concluded that by adding water-soluble polymer solution, the fracturing fluid has better temperature resistance, salt resistance and shear resistance, and can maintain stable performance in complex underground environments. At the same time, polyacrylamide can significantly improve the sand carrying capacity, resistance reduction performance and gel breaking performance of the fracturing fluid;

[0091] By adding fluorinated monomers, the fracturing fluid has lower viscosity and good fluidity, which improves the fracturing effect and promotes flowback. The introduction of fluorinated monomer modifier solution can enhance the hydrophobicity of the molecules, which helps to reduce the interaction between water molecules and drag reducer molecules, thereby reducing the influence of salt ions on drag reducer molecules.

[0092] By adding modifiers to nanomaterials, a polymer film can be directly formed on the surface of the nanomaterials by chemical bonding, changing its surface properties, thereby enhancing the compatibility of the nanomaterials with the polymer matrix, and helping to maintain the stability and shear resistance of the fracturing fluid at high temperatures. Figure 2 and Figure 3 It can be seen that the dispersion time of JHFR-2 nanocomposite liquid drag reducer in clean water and flowback fluid is less than 30s. Figure 3The figure shows the dissolution of three drag reducers in clean water and flowback fluid. It can be observed that the JHFR-2 nanocomposite liquid drag reducer solution (JHFR-2 nanocomposite liquid drag reducer is a green, clean, efficient and fast-dissolving drag reducer developed for shale gas development. It is a core additive in the slick water fracturing fluid system) is colorless and transparent; there are a few dispersed small particles in the powder drag reducer solution; the oil-based drag reducer solution is a bit turbid, and after being placed for a period of time, a layer of white floating matter will appear on the upper layer. Therefore, the dispersion time of JHFR-2 nanocomposite liquid drag reducer is significantly better than that of oil-based drag reducer and powder drag reducer. Therefore, the fracturing fluid prepared with JHFR-2 nanocomposite material has a good effect not only in clean water, but also in flowback fluid. In addition, the promotion and application of JHFR-2 is conducive to the recycling and environmental protection of flowback fluid, with obvious economic benefits.

[0093] 1. High temperature resistance: refers to the highest temperature at which the fracturing fluid can still maintain good performance at a specific temperature.

[0094] 2. Stability (viscosity change after 24 hours): indicates the percentage change in viscosity of the fracturing fluid relative to the initial viscosity after it has been left at room temperature for 24 hours. A negative value indicates an increase in viscosity, and a positive value indicates a decrease in viscosity.

[0095] 3. Sand carrying capacity (sand settling time): It refers to the time required for sand particles in the fracturing fluid to begin to settle significantly under specific conditions. The longer the time, the stronger the sand carrying capacity.

[0096] 4. Viscosity: It indicates the viscosity value of fracturing fluid and is an important indicator to measure the flow properties of fracturing fluid.

[0097] 5. Shear resistance (viscosity retention rate after 170s-1 shear): It indicates the retention percentage of the viscosity of the fracturing fluid relative to the viscosity before shearing after experiencing a high shear rate of 170s-1. The higher the retention rate, the better the shear resistance.

[0098] 6. Ionic strength: A measure of the ion concentration in the fracturing fluid, which is related to the electrolyte balance and osmotic pressure of the fracturing fluid.

[0099] The above are only specific embodiments of the present invention, but the technical features of the present invention are not limited thereto. Any simple changes, equivalent replacements or modifications made based on the present invention to solve basically the same technical problems and achieve basically the same technical effects are all included in the protection scope of the present invention.

Claims

1. A method for preparing a self-flowing high-efficiency fast-dissolving drag-reducing fracturing fluid system, characterized in that: The production steps include: Step 1: adding a certain amount of water-soluble polymer to water and stirring until completely dissolved to obtain a water-soluble polymer solution; Step 2: mixing the fluorinated monomer with an organic solvent and a surfactant to prepare a fluorinated monomer modifier solution through a free radical polymerization reaction; Step 3: Adding a modifier to an appropriate amount of nanomaterials can directly combine with the surface of the nanomaterials by chemical bonding and form a polymer film on the surface of the nanomaterials, thereby changing its surface properties and improving its compatibility with the polymer matrix; Step 4: dissolving an appropriate amount of the modified nanomaterial in step 3 and an appropriate amount of the polymer matrix in an organic solvent, mixing them evenly by ultrasonic means, and the sound wave range is 30kHz to 80kHz, and then volatilizing and drying the final solvent, and the drying temperature range is 30°C to 40°C, and finally obtaining a polymer nanocomposite material; Step 5: Add the following components in weight percentage into the reactor in sequence: 45% to 50% of the water-soluble polymer solution obtained in step 1, 27% to 29% of the fluorinated monomer modifier solution obtained in step 2, 11% to 12% of the polymer nanocomposite material obtained in step 4, 2% to 3% of the dispersant, 1.8% to 1.9% of the inorganic salt, 1.2% to 1.3% of the cross-linking agent and the balance of water, stir and mix thoroughly to obtain a fracturing fluid; Step 6: Use a pH regulator to adjust the pH value of the fracturing fluid to between 7 and 8; Step 7: Filter the prepared fracturing fluid through a filter to remove impurities and undissolved particles, and then package it into a finished product; Wherein, the water-soluble high molecular polymer is polyacrylamide monomer, and the nano material is silicon dioxide nano material.

2. The method for preparing a self-flowing high-efficiency fast-dissolving drag-reducing fracturing fluid system according to claim 1, characterized in that: The mass ratio of the polyacrylamide monomer to water is 3:1000.

3. The method for preparing a self-flowing high-efficiency fast-dissolving drag-reducing fracturing fluid system according to claim 1, characterized in that: In step 2, the organic solvent is acetone, the fluorine-containing monomer is perfluoroacrylate, the surfactant is a fluorine-containing surfactant, and the mass ratio of the acetone, perfluoroacrylate and fluorine-containing surfactant is 30:12:

7.

4. The method for preparing a self-flowing high-efficiency fast-dissolving drag-reducing fracturing fluid system according to claim 1, characterized in that: The modifier is polyethylene glycol, and the mass ratio of the nano material to the modifier is 8:

1.

5. The method for preparing a self-flowing high-efficiency fast-dissolving drag-reducing fracturing fluid system according to claim 1, characterized in that: The polymer matrix is ​​a mixture of epoxy resin and polyimide, and the mass ratio of the epoxy resin to the polyimide is 1:

1.

6. The method for preparing a self-flowing high-efficiency fast-dissolving drag-reducing fracturing fluid system according to claim 1, characterized in that: The organic solvent in step 4 is N,N-dimethylformamide, and the mass ratio of the pre-synthesized nanomaterial and the polymer matrix is ​​2:

7.

7. The method for preparing a self-flowing high-efficiency fast-dissolving drag-reducing fracturing fluid system according to claim 1, characterized in that: The pH regulator is sodium hydroxide and acetic acid solution.

8. The method for preparing a self-flowing high-efficiency fast-dissolving drag-reducing fracturing fluid system according to claim 1, characterized in that: The dispersant is a nonionic surfactant, the inorganic salt is calcium chloride, and the cross-linking agent is borate.

Citation Information

Patent Citations

  • Fluorine-modified water-in-water high-backflow low-damage slickwater fracturing fluid system drag reducer

    CN104877072A

  • Low-friction drag composite nano-proppant and preparation method thereof

    CN108517205A